Fostering Exceptional Entrepreneurial Spirits: Unveiling Parental Strategies For Children With Disabilities - Ainun Fuad; Sudarmiatin Sudarmiatin; Rizky Firmansyah (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Education plays a central role in shaping children's values, norms, and character. For deaf children in Mojokerto Regency, double challenges such as job uncertainty and limited access to entrepreneurship education stand out. This descriptive qualitative research aims to explore the role of parents in instilling entrepreneurial spirit in deaf children, filling knowledge gaps, and providing practical guidance. Involving learners with disabilities, data was collected through observation, interviews, and documentation in several inclusion schools. Data analysis uses data reduction, display, and inference, with triangulation for validity. Results show parents create an inclusive environment, encouraging children's independence and creativity. The documentation describes the implementation of entrepreneurial parenting. These findings support the effectiveness of parents in shaping the entrepreneurial spirit of deaf children, contributing to the understanding of inclusive education practices and fostering the talents of children with special needs. The implication is to support holistic and inclusive education policies..